2021
DOI: 10.1177/08959048211049428
|View full text |Cite
|
Sign up to set email alerts
|

The Signaling Power of Unexcused Absence from School

Abstract: State and national school accountability policies situate preventing chronic absenteeism on par with meeting state standardized test benchmarks. We question relying on school attendance as both a component of accountability policies and a means of enhancing equity in schools. Our research suggests out-of-school factors unrelated to missed instruction account for most of the associations between absences and test score achievement—with unexcused absences driving those associations. Excessive absences—and partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…Aside from learning loss, truancy may be associated with individual factors such as problem behaviors (Eaton, Brener, and Kann 2008; Hallfors et al 2002; Rocque et al 2017; Zhang et al 2007), structural challenges such as neighborhood disadvantage, out-of-school harms, and school-level policies that disproportionally penalize disadvantaged groups (McNeely et al 2021; Mireles-Rios, Rios, and Reyes 2020; Singer et al 2021). These factors, in turn, are associated with educational outcomes and thus may exacerbate the harmful effects of truancy on pupils’ academic achievement (Dornbusch et al 2001; Fergusson and Horwood 1995; Jeynes 2002; Pyne et al 2023). Additionally, students who miss school due to truancy may experience greater alienation from their peers, teachers, and schools (Finn 1989; Wilson et al 2008) and possibly receive limited support to help with learning (Roorda and Koomen 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from learning loss, truancy may be associated with individual factors such as problem behaviors (Eaton, Brener, and Kann 2008; Hallfors et al 2002; Rocque et al 2017; Zhang et al 2007), structural challenges such as neighborhood disadvantage, out-of-school harms, and school-level policies that disproportionally penalize disadvantaged groups (McNeely et al 2021; Mireles-Rios, Rios, and Reyes 2020; Singer et al 2021). These factors, in turn, are associated with educational outcomes and thus may exacerbate the harmful effects of truancy on pupils’ academic achievement (Dornbusch et al 2001; Fergusson and Horwood 1995; Jeynes 2002; Pyne et al 2023). Additionally, students who miss school due to truancy may experience greater alienation from their peers, teachers, and schools (Finn 1989; Wilson et al 2008) and possibly receive limited support to help with learning (Roorda and Koomen 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A contrary perspective is that absences do not primarily influence achievement due to learning loss. Instead, the association between absences and achievement reflects the effects of multiple out-of-school challenges that absent students face (Pyne et al 2023; Singer et al 2021).…”
mentioning
confidence: 99%
“…In addition, cutoffs tend to minimize key differences between student groups and ignore more subtle differences; a dominant student group at a school may be largely present (e.g., 95%) whereas a minoritized group may be less present (e.g., 70%), but the overall school attendance rate (90%) could be considered non-problematic and not in need of intervention (Gee, 2018). Other nuanced variables are minimized as well, particularly circumstances beyond a family's control such as transportation vulnerability and lack of safe routes to and within schools, as well as situations where school absence is an adaptive choice for a student (e.g., to support a family economically) (Birioukov, 2016;Pyne et al, 2021). In related fashion, cutoffs are typically used for punitive purposes and are not generally linked to specific restorative interventions, particularly for vulnerable students who must overcome multiple daily challenges simply to maintain semiregular attendance (Hutt, 2018).…”
Section: Demarcating School Attendance Problems Historical Categoriesmentioning
confidence: 99%
“…First, it allows us to distinguish, to some extent, why absences may occur. Several empirical studies highlight the importance of di↵erentiating between unexcused and excused absences when examining academic engagement among students (Gottfried, 2009;Liu and Loeb, 2021;Pyne et al, 2021). For instance, Pyne et al (2021) found that unexcused absences are detrimental toward yearly academic growth, while excused absences are only modestly associated with declines in academic growth.…”
Section: Excused Vs Unexcused Absencesmentioning
confidence: 99%
“…Several empirical studies highlight the importance of di↵erentiating between unexcused and excused absences when examining academic engagement among students (Gottfried, 2009;Liu and Loeb, 2021;Pyne et al, 2021). For instance, Pyne et al (2021) found that unexcused absences are detrimental toward yearly academic growth, while excused absences are only modestly associated with declines in academic growth. Similarly, Gottfried (2009) reported that among students with an equal number of absences, those with a higher proportion of unexcused absences (relative to excused ones) had lower math achievement relative to those with a higher proportion of excused absences.…”
Section: Excused Vs Unexcused Absencesmentioning
confidence: 99%